Skin Lesions in Children with Coronavirus Infection (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Based on the analysis of literature descriptions of clinical observations of dermatological symptoms in patients with COVID-19, skin lesions can be the first signs of the onset of COVID-19. No direct connection between exanthema in COVID-19 and an allergic history has been identified. Skin stigmas of COVID-19 in children have certain clinical signs. The main mechanisms of exanthema development are associated with an inflammatory reaction of the skin vessels: capillary dilation, blood stasis, increased vascular permeability with the development of hemorrhages and edema, necrosis of the epidermis and dermis, dystrophic changes in cells. The use of systemic glucocorticosteroids contributed to the relief of exanthema. Increasing the awareness of pediatricians about skin changes associated with COVID-19 will allow more effective detection of the infection and care for children.